How does the sojourner teach the character of God? - Gallant, Anna Grace, 1974- (St. Louis, Missouri : Covenant Theological Seminary, 2007)
1 online resource (PDF(ix, 83 leaves)); Abstract; Typescript (photocopy); Thesis (M.A.E.T.)--Covenant Theological Seminary, 2007; Bibliography: leaves 80-83